Museologia social e comunitária na Paraíba: memoriação, lutas e resistências - Tolentino, Átila Bezerra (RITUR - Revista Iberoamericana de Turismo, 2023)
This article presents cases and initiatives of community museums in Paraíba-Brazil, outlining their specificities and how the configuration of collective memories of historically subordinated social groups is linked to their struggles, demands and resistances. To do so, it starts with a brief setting of the debate around social museology and what a community museum consists of. Then, the experiences of the Museu Comunitário Vivo Olho do Tempo, the Museu Quilombola do Ipiranga, the Museu do Patrimônio Vivo da Grande João Pessoa and the Memorial das Ligas e Lutas Camponesas are described. It is argued that these are exemplary cases of community museology in the State of Paraíba, given that its musealization processes are strongly linked to social struggles and demands, as well as to the preservation of the memory of historically subordinated and invisible groups and communities in institutional mechanisms of an official memory. From the thinking of social psychologist Ecléa Bosi, it is understood that community museums in Paraíba work with “memoriaction”, taking into account the junction of the words memory + action, in the sense that memory is work, therefore, it is active, acts and interferes in the processes of representations at all times in the present, including the struggles and anxieties of different social groups.